2020
DOI: 10.1111/mec.15332
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific expression of fertilization genes in the crown‐of‐thorns Acanthaster cf. solaris: Unexpected evidence of hermaphroditism in a coral reef predator

Abstract: The characterization of gene expression in gametes has advanced our understanding of the molecular basis for ecological variation in reproductive success and the evolution of reproductive isolation. These advances are especially significant for ecologically important keystone predators such as the coral‐eating crown‐of‐thorns sea stars (COTS, Acanthaster) which are the most influential predator species in Indo‐Pacific coral reef ecosystems and the focus of intensive management efforts. We used RNA‐seq and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 107 publications
(194 reference statements)
3
9
0
Order By: Relevance
“…The PCA confirmed that each individual clustered with its corresponding group, either the hermaphroditic C. hystera , or the gonochoric C. pentagona males or C. pentagona females (Figure 2). The expression of GRGs (Table ) was consistent with that result and with the gonad types of each individual: hermaphroditic gonads of C. hystera showed expression of GRGs that are characteristic of both sperm and eggs; and the gonochoric testes or ovaries of C. pentagona showed expression of either sperm‐ or egg‐specific GRGs but not both (for a counterexample see Guerra et al, 2020). Information on the differential expression analysis and polymorphism is found in the supplement (Tables and and Figure ).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The PCA confirmed that each individual clustered with its corresponding group, either the hermaphroditic C. hystera , or the gonochoric C. pentagona males or C. pentagona females (Figure 2). The expression of GRGs (Table ) was consistent with that result and with the gonad types of each individual: hermaphroditic gonads of C. hystera showed expression of GRGs that are characteristic of both sperm and eggs; and the gonochoric testes or ovaries of C. pentagona showed expression of either sperm‐ or egg‐specific GRGs but not both (for a counterexample see Guerra et al, 2020). Information on the differential expression analysis and polymorphism is found in the supplement (Tables and and Figure ).…”
Section: Resultssupporting
confidence: 79%
“…It remains possible that new GRGs not previously described and not analyzed in this study, including GRGs created through the process of neofunctionalization, may have participated in that speciation event. In particular, the binding region of REJ1 is expected to interact with the ARIS protein complex in the egg coat, but ARIS1 , ARIS2 , and ARIS3 (which are abundantly expressed in other sea star oocytes; Guerra et al, 2020; Hart & Foster, 2013) are not expressed in Cryptasterina ovaries. This gap in evidence suggests that ARIS genes in Cryptasterina have diverged so strongly from those of other sea stars that they cannot be recognized by sequence‐similarity searches using BLAST, or that the function of the ARIS proteins in the egg coat has been replaced by neofunctionalization of other genes.…”
Section: Discussionmentioning
confidence: 99%
“…The resilience of the herbivorous juvenile COTS to coral scarcity adds to the suite of remarkable traits that may contribute to its boom-bust dynamics. Larval plasticity is seen in cloning and body form and potential nutritive augmentation from a phototropic microbiome to dissolved organic matter [29][30][31][32], and some adults may be hermaphrodites [33]. That the herbivorous phase has the potential to accumulate in the reef infrastructure for years to seed an outbreak should be considered alongside the current larva-centric model of COTS outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found three pairs of individuals in Ogasawara population were possible clonal or genetically very close individual (Table 1 and Supplementary Figure 2). It is also notable that we also found one pair of possible clonemates in Tatsukushi population where previous study found hermaphrodites (Guerra et al, 2020). Although we need more precise analysis to identify true clonemates, it is possible that inbreeding including self-fertilization or larval cloning also partly facilitated the initiation of population outbreak in the oceanographically isolated Ogasawara populations.…”
Section: Possible Causes Of Population Outbreak In Ogasawaramentioning
confidence: 48%
“…Recently, self-fertilization and/or clonal propagation hypothesis has been proposed by Guerra et al (2020) to explain the cause of primary outbreak as evidenced by the existence of hermaphrodites and the finding of possible larval cloning of A. cf. solaris (Allen et al, 2019).…”
Section: Possible Causes Of Population Outbreak In Ogasawaramentioning
confidence: 99%